Kajian Literatur: Penyebab Kecemasan Mahasiswa Saat Menghadapi Ujian Praktek - Wilasita, Ayu Kusuma; Susilawati, Luh Kadek Pande Ary (Peneliti.net, 2024)
Students are expected to be able to become developed human resources and be able to serve society in the future. However, before reaching the personal stage expected by the institution, students often experience unpleasant experiences such as anxiety when practicing. Anxiety is an emotional state characterized by physiological arousal, unpleasant feelings and feelings of worry that something bad will happen soon. This literature review was carried out to collect more research data and the causes of anxiety in students taking practical exams in certain subjects. The method used for this literature review search was through Google Scholar and Research Gate with journal criteria of a maximum of 10 years. The research sample that is the focus of this literature review is students who took practical exams in their courses. The results of the literature review show that the causes of anxiety are divided into two, namely internal factors and external factors.